To determine an equivalent system of equations for System A and System B, we first need to clarify and examine the given equations.
From the information, System A:
- \(-x + y = 11\)
- \(x + y = 11\)
System B:
- \(x + y = 11\)
An equivalent system means that we need to manipulate the original equations while keeping the solutions the same. We can do this through algebraic transformations.
Let's analyze the options given:
-
\(2y = 12\): This simplifies to \(y = 6\). This does not relate to the original equations as it is not derived from them.
-
\(2x + 2y = 12\): This can be divided by 2 to yield \(x + y = 6\). This is not equivalent to \(x + y = 11\).
-
\(-x - y = -1\): We can rewrite this as \(x + y = 1\) by multiplying the entire equation by -1. This is also not equivalent to the original equations.
-
\(-2x - 2y = -22\): Dividing through by -2 gives \(x + y = 11\), which is indeed equivalent to the original equation \(x + y = 11\).
Thus, the correct option that creates a true equivalent system is:
4. -2x - 2y = -22.